2005
DOI: 10.5194/angeo-23-3513-2005
|View full text |Cite
|
Sign up to set email alerts
|

Motion of the dayside polar cap boundary during substorm cycles: II. Generation of poleward-moving events and polar cap patches by pulses in the magnetopause reconnection rate

Abstract: Abstract. Using data from the EISCAT (European Incoherent Scatter) VHF and CUTLASS (Co-operative UK TwinLocated Auroral Sounding System) HF radars, we study the formation of ionospheric polar cap patches and their relationship to the magnetopause reconnection pulses identified in the companion paper by Lockwood et al. (2005). It is shown that the poleward-moving, high-concentration plasma patches observed in the ionosphere by EISCAT on 23 November 1999, as reported by Davies et al. (2002), were often associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 65 publications
4
53
0
Order By: Relevance
“…5d, where fast flows of >~1500 m/s are predominantly seen during large |By| and small |Bz|. Under a large IMF By condition, it has been observed that mesoscale flows in the cusp region propagate poleward, and this has been suggested to be due to large tension force in dayside reconnection under large IMF |By| (Sandholt et al 2004;Lockwood et al 2005;Rinne et al 2010;Zhang et al 2011Zhang et al , 2013b. Combining with our observation, these mesoscale flows may move far away from the noon meridian and then propagate into the polar cap.…”
Section: Imf By and Bz Dependencesupporting
confidence: 70%
See 2 more Smart Citations
“…5d, where fast flows of >~1500 m/s are predominantly seen during large |By| and small |Bz|. Under a large IMF By condition, it has been observed that mesoscale flows in the cusp region propagate poleward, and this has been suggested to be due to large tension force in dayside reconnection under large IMF |By| (Sandholt et al 2004;Lockwood et al 2005;Rinne et al 2010;Zhang et al 2011Zhang et al , 2013b. Combining with our observation, these mesoscale flows may move far away from the noon meridian and then propagate into the polar cap.…”
Section: Imf By and Bz Dependencesupporting
confidence: 70%
“…It is known that for large, negative By, the boundary between dawn and dusk convection cells is shifted toward dawn in the southern hemisphere (Reiff and Burch 1985;Lyons et al 1996) and toward dusk in the northern hemisphere (Weimer 2005). Additionally, the previous case studies have shown the IMF By-related formation of polar cap patches (Lockwood et al 2005;Zhang et al 2011Zhang et al , 2013b. In our study, we statistically showed that the departing points of these patches from the poleward boundary of auroral oval are associated with IMF By, and moreover, the airglow patches that depart at <9 MLT are with strong negative By.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The difficulty with patch segmentation is to explain the low density regions between patches (Lockwood et al, 2005b). The mechanisms that have been suggested to segment the intake of cold solar EUV ionized plasma into the cusp throat can be divided in three families:…”
Section: Introductionmentioning
confidence: 99%
“…Several observation techniques have been used for patch studies, such as direct electron density measurements by ionosonde (Buchau et al, 1983;Dandekar and Bullett, 1999;Dandekar, 2002), incoherent scatter radar (e.g. Valladares et al, 1994Valladares et al, , 1996Valladares et al, , 1998Carlson et al, 2002Carlson et al, , 2004Carlson et al, , 2006Lockwood and Carlson, 1992;Lockwood et al, 2005aLockwood et al, , 2005bOksavik et al, 2006a), and ionospheric tomography (Walker et al, 1999;Pryse et al, 2004), 630.0-nm airglow intensity that is proportional to electron density (Weber et al, 1984;Harris, 1995, 1996;McEwen et al, , 2004Lorentzen et al, 2004), and more indirectly by HF coherent scatter radars of the SuperDARN network (Rodger et al, 1994;Ogawa et al, 1998;Rodger and Graham, 1996;Milan et al, 2002Milan et al, , 2005Oksavik et al, 2006a). The latter technique does not provide a measurement of the electron density but gives the backscatter power from irregularities on electron density gradient associated E×B drift instability (Tsunoda, 1988;Chaturvedi and Ossakow, 1981).…”
Section: Introductionmentioning
confidence: 99%